Gestión del inventario del Almacén Babahoyo en el período 2020-2021 - Choto Barragán, Jennifer Rosalía (2023)
Inventory management, a critical element of the supply chain, is the tracking of inventory from the time of manufacture to warehouses, and from these facilities to the point of sale. The present case study followed the objective of analyzing inventory management to improve the control of the Babahoyo Warehouse Company during the 2020-2021 period, for which a qualitative-quantitative investigation was carried out through the processing of non-accounting information that are the different bibliographic results investigated and the processing of quantitative information that was applied through financial ratios such as the turnover rate and the coverage rate. According to the results obtained from the calculation of the turnover rate in the 2020 and 2021 periods, it was possible to show that in the 2020 period the inventory rotated 3 times in a year, that is, every 4 months the inventory of stocks was renewed while that for the 2021 period it can be seen that the inventory rotated 2 times in a year, that is, inventory stocks were renewed every 6 months, there is evidence of a decrease in inventory rotation of 1 time less compared to the previous year. In conclusion, the Babahoyo Warehouse must carry out an inventory management plan that is much more feasible than the one it currently manages, due to the fact that on several occasions it does not request enough merchandise from suppliers and, according to the demand index, it does not cover the total stock of the investment. , that is to say that at the end of the year there is a lot of demand that has not been met.